The truth, but not yet: avoiding naïve skepticism via explicit communication of metadisciplinary aims. Issue 3 (3rd April 2019) - Wright, Jake
ABSTRACT: Introductory students regularly endorse naïve skepticism – unsupported or uncritical doubt about the existence and universality of truth – for a variety of reasons. Though some of the reasons for students' skepticism can be traced back to the student – for example, a desire to avoid engaging with controversial material or a desire to avoid offense – naïve skepticism is also the result of how introductory courses are taught, deemphasizing truth to promote students' abilities to develop basic disciplinary skills. While this strategy has a number of pedagogical benefits, it prevents students in early stages of intellectual development from understanding truth as a threshold concept. I argue that we can make progress against naïve skepticism by clearly discussing how metadisciplinary aims differ at the disciplinary and course levels in a way that is meaningful, reinforced, and accessible.